Development of electronic portfolios to assess concept mastery and creative thinking on project-based acid-based concepts - Aini, Nisa Qurrata; Nahadi, Nahadi; Fatimah, Soja Siti (Jurnal Pendidikan Kimia, 2024)
The purpose of the study was to develop an electronic portfolio instrument to assess concept mastery and creative thinking on project-based acid-base materials. The research participants are class XI, who will study acid-base materials. This research uses the 4D Research and Development model which are carried out up to stage 3 (Define, Design, and Development). On the define stage, a literature study, a field survey, material analysis, indicator analysis, and task analysis were conducted. The design stage designed grids and assessment rubrics, the preparation tasks consisting of four: making papers, practicum reports, posters, and concept maps. The design stage compiled an electronic portfolio instrument. The developmental stage conducts quality tests: initial development test, expert validity test obtained a CVR value of 1.00, reliability test with inter-rater obtained a Cronbach Alpha value between 0.652 and 1.000. After the electronic portfolio instrument was valid and reliable, a limited trial was conducted with N-Gain scores of task 1, task 2, task 3, and task 4, respectively: 0.17 (low), 0.13 (low), 0.46 (medium), and 0.32 (medium). The overall average of the pretest and posttest N-Gain scores is 0.90, with a higher category. This electronic portfolio instrument based on Project-Based Learning (PjBL) is expected to help teachers assess tasks on concept mastery and students' creative thinking on acid-based materials.